Beyond Hate: Confronting Islamophobia and Anti-Muslim Racism in Social Work - Elkassem, Siham (Intersectionalities, 2024)
Canada has a significant problem with Islamophobia and anti-Muslim racism (AMR), holding the alarming distinction of having the highest rate of targeted killings of Muslims among G7 countries. Beyond personal fear and hatred of Muslims and Islam, Islamophobia and AMR are deeply ingrained in institutional and structural systems, perpetuating violence and discrimination. This paper challenges the conventional view of Islamophobia and AMR as simply an individual moral issue, arguing instead that it is a form of racial and colonial violence occurring across multiple levels of Canadian society. AMR intersects with other forms of oppression, including sexism, anti-Arab, anti-Black, and anti-Brown racism, xenophobia, homophobia, and transphobia. Despite social work’s stated commitment to social justice, the profession has failed to effectively address AMR due to its own ongoing legacy of racism, white supremacy, and coloniality. To truly uphold its stated commitments to equity and human rights, social work must confront AMR at all levels. Grounded in critical race and anti-colonial theory, this paper illustrates how AMR is a multifaceted issue. While advancing a framework for addressing AMR within social work, this paper emphasizes the need for a comprehensive approach that encompasses direct practice, policy and community work, research, and education. Recommendations include adopting an antiMuslim racism approach that includes strategies that can be used to confront AMR and identify key challenges and opportunities for transformative change within social work.